A constituição identitária de Olga Benário: uma abordagem pragmática - Serpa, Maria Valquíria Faria (2008)
This study aimed at investigating the way the construction of several Olga Benário s identity positions occurs, from the politics of nomination/predication and the representation found in the linguistic materiality of some biographical texts: the books Olga, by Fernando Morais (2004) and Camaradas, by William Waack (2004); the essays Olga , by Rita Buzzar (1995) and Olga Benário Prestes, minha mãe and Olga: revolucionária sem perder a ternura , both written by Anita Leocádia Prestes, which have been published in 1995 and 2004 respectively. This investigation had also the purpose of identifying the systems of values and beliefs which are in play in the legitimation and in the deletion of several Olga s identity aspects. It intended to present how these aspects are described and how they identify that militant woman by means of the politics of representation which are subjacent to the politics of nomination/predication used in each of the analyzed texts and which are directly related to the process of Olga Benário s identity construction, afterwards, Olga Benário Prestes. Finally, the developed analysis configured itself as a research of analytical, critical and descriptive character since it is based on post-structuralist theoretical approaches about the concept of identity, interpreted and described the process of construction of the aspects which identify Olga Benário. The above mentioned analysis took into consideration the social-historical, cultural and ideological manifestations of the moment when Olga s militancy had taken place, even the context of the biographical texts have been written. Thus, it was possible to confirm the following hypothesis: some Olga s identity aspects are deleted and others are put in evidence in the texts, depending on the convenience of the politics of representation of each analyzed source, since every particular politics of representation is always molded by ideological, social and political questions. As a result, Olga s portrait always presents itself as multifaceted. The several Olga s identities were noticed, even though there had been the necessity of each writer to make Olga s identities essential. The parameter of this research was that from Pragmatics, related to the discussion of the performative character of language and to the act of nominating/predicating (AUSTIN, 1990); to the politics of representation (RAJAGOPALAN, 2002, 2003). Besides, this research took use of the notions of identity and difference which were discussed from the perspective of cultural and linguistic studies.